ENGLISH English Language - Agustin, Rista Reza Virzinia; Mufidah, Ilma; Martini, Sri; Caesaron, Dino (Universitas Serang Raya, 2024)
A market levy is a type of general service levy collected from traders to cover the costs of using market facilities and obtaining permits from the local government. The benefit of implementing digital levy payment is that the levy payment service can be accessed online, facilitating payment transactions for traders. However, the researchers observed issues in the Trade Sector of the West Bandung Regency’s Department of Industry and Trade, particularly regarding the inefficient collection of market levies. Using a digital fee collection system can reduce several risks for the government, such as preventing leakage of fees that generally occurs with manual collection, errors in refunds and calculations, and providing protection during cash collection. The implementation of this digital levy aims to maximize Regional Original Revenue and reorganize the market system. This digital payment system was designed using the design thinking method. The design thinking method has effectively helped identify user needs and create solutions. The usability testing results using the Useberry application for the West Bandung Industry and Trade Office’s levy application received positive responses, as all 10 respondents of end users completed the tasks given. Furthermore, the 26 UEQ items were grouped into six categories. The assessment of the six categories is generated good scores. Based on this, the user experience of the West Bandung Industry and Trade Office’s levy application can be categorized as good.